A Needle‐Type Microrobot for Targeted Drug Delivery by Affixing to a Microtissue. Issue 7 (3rd March 2020) - Lee, Seungmin; Kim, Jin‐young; Kim, Junyoung; Hoshiar, Ali Kafash; Park, Jongeon; Lee, Sunkey; Kim, Jonghyun; Pané, Salvador; Nelson, Bradley J.; Choi, Hongsoo
Abstract: A needle‐type microrobot (MR) for targeted drug delivery is developed to stably deliver drugs to a target microtissue (MT) for a given period time without the need for an external force after affixing. The MRs are fabricatedby 3D laser lithography and nickel (Ni)/titanium oxide (TiO2 ) layers are coated by physical vapor deposition. The translational velocity of the MR is 714 µm s −1 at 20 mT and affixed to the target MT under the control of a rotating magnetic field. The manipulability of the MR is shown by using both manual and automatic controls. Finally, drug release from the paclitaxel‐loaded MR is characterized to determine the efficiency of targeted drug delivery. This study demonstrates the utility of the proposed needle‐type MR for targeted drug delivery to MT with various flow rates in vitro physiological fluidic environments. Abstract : A needle‐type microrobot is fabricated by 3D laser lithography for stable drug delivery. The drug‐loaded microrobot can be fixed to a target microtissue by swimming in a corkscrew motion under a rotating magnetic field. The results demonstrate the potential of the needle‐type microrobot to improve targeted drug delivery to microtissue with various flow rates in vitro physiological fluidic environments.